Impact of the Co : Cu Ratio in CoCu‐Containing Oxidic Solids on their Activity for the Water‐Splitting Reaction. Issue 8 (4th July 2017) - Polyakov, Mykola; Surkus, Annette‐Enrica; Maljusch, Artjom; Hoch, Sascha; Martin, Andreas
Abstract: Noble metal free bimetallic CoCu‐containing water splitting catalysts for the oxygen evolution reaction (OER) in basic media with different Co : Cu ratios were synthesized. A simple sol‐gel method with citric acid as a multipurpose chelating and reduction agent was used. The subsequent thermal treatment was carried out in an oxygen‐deficient atmosphere (pyrolysis). The catalysts were characterized by rotating disc electrode (RDE) OER measurements, N2 adsorption, XRD, XPS, TEM, DLS and elemental analyses. The highest activity in the OER was achieved with a Co : Cu ratio of 5 (47 A gcatalyst −1 at 1.6 V versus the reversible hydrogen electrode). This is the first time that such high activity has been reported. These transition metal oxide catalysts might be promising candidates as an anode material in alkaline water electrolyzers. Higher and lower Co : Cu ratios revealed less activity. Abstract : Copper: Less is more? Noble metal free bimetallic CoCu‐containing water splitting catalysts for the oxygen evolution reaction (OER) in basic media were synthesized. The highest activity in OER was achieved with a Co : Cu ratio of 5 (47 A gcatalyst −1 at 1.6 V versus RHE).